Resposta :
Resposta:
[tex]\textsf{Leia abaixo}[/tex]
Explicação passo a passo:
[tex]\mathsf{f(x) = 2^{2x - 4}}[/tex]
[tex]\mathsf{f(-1) = 2^{2(-1) - 4}}[/tex]
[tex]\mathsf{f(-1) = 2^{-2 - 4}}[/tex]
[tex]\mathsf{f(-1) = 2^{-6}}[/tex]
[tex]\mathsf{f(-1) = \dfrac{1}{2^{6}}}[/tex]
[tex]\boxed{\boxed{\mathsf{f(-1) = \dfrac{1}{64}}}}[/tex]
Explicação passo-a-passo:
[tex]f(x) = 2 {}^{2x - 4} [/tex]
[tex]f( - 1) = 2 {}^{(2 \times - 1 - 4)} [/tex]
[tex]f( - 1) = 2 {}^{( - 2 - 4)} [/tex]
[tex]f( - 1) = 2 {}^{ - 6} [/tex]
Transformando como expoente positivo.
[tex]f( - 1) = \dfrac{1}{2 {}^{6} } [/tex]